Animal welfare issues on the use of rabbits in an animal assisted therapy program for children - LOUKAKI (Κ. ΛΟΥΚΑΚΗ) K.; KOUKOUTSAKIS (Π. ΚΟΥΚΟΥΤΣΑΚΗΣ) P.; KOSTOMITSOPOULOS (Ν. ΚΩΣΤΟΜΗΤΣΟΠΟΥΛΟΣ) N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Animal Assisted Therapy (AAT) is a method of complementary treatment in the rehabilitation of many human illnesses and conditions. Although the dog is the most widely used therapy animal that is used in AAT program, the rabbit can also be used as an alternate animal species and complementary therapy for many diseases. It is an intelligent, human friendly and playful small animal, easily socialized and transported. Also, the rabbit has very good communication through its body language. A special bond, also, exists between children and rabbits, and in the animal world of children, the rabbit is a very popular animal mainly through children’s literature. As a result, rabbits elicit positive feelings in children and enhance their imagination. Based on previousexperience from an AAT program with rabbits in a children’s hospital, the rabbit can be easily accepted by children with emotional or physical problems. In order for an AAT program with a rabbit to be a success, it is very important to guarantee good health and normal behaviour of the rabbit, as well as its proper welfare. The contribution and participation of a veterinarian during the design and the implementation of the program are, also, very important for assuring the success of an AAT program with rabbits.